2012
DOI: 10.1253/circj.cj-11-1444
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoglucomutase Activity as a Novel Biomarker in Patients With Acute Myocardial Infarction

Abstract: Background: Phosphoglucomutase (PGM), a key enzyme in cellular glucose utilization and energy homeostasis, has been reported to show a relationship with oxidative stress. However, the clinical importance of PGM activity has not been investigated in patients with ischemic heart disease (IHD). The aim of the present pilot study was to clarify whether PGM activity has potential as a cardiovascular risk predictor in patients with IHD. Methods and Results:The levels of serum PGM activity in 237 patients with IHD (6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…In addition, Preisler et al [41] implied that the liver might be affected by PGM deficiency and that reduced liver glucose levels might contribute to the low blood glucose levels observed during exercise in this condition. In this regard, polymorphism in PGM has been reported to be useful as a genetic biomarker for alcoholic cirrhosis [42], ischemic heart disease [43], and obesity disorders [44, 45]. The results of the current study show that training exercise increased the protein content of PGM in the livers of old rats, which likely contributed to the improved glycolytic metabolism of these animals, despite their advanced cirrhosis.…”
Section: Discussionmentioning
confidence: 51%
“…In addition, Preisler et al [41] implied that the liver might be affected by PGM deficiency and that reduced liver glucose levels might contribute to the low blood glucose levels observed during exercise in this condition. In this regard, polymorphism in PGM has been reported to be useful as a genetic biomarker for alcoholic cirrhosis [42], ischemic heart disease [43], and obesity disorders [44, 45]. The results of the current study show that training exercise increased the protein content of PGM in the livers of old rats, which likely contributed to the improved glycolytic metabolism of these animals, despite their advanced cirrhosis.…”
Section: Discussionmentioning
confidence: 51%
“…16 Therefore, PGM activity might indicate myocardial damage, thrombus formation, and the presence of inflammation associated with coronary plaque rupture. Their pilot study suggested that PGM activity, including that of the PGM isoform, might have useful diagnostic applications in the acute phase of AMI patients, although further studies would be required to elucidate the findings in detail.…”
Section: Article P 2197mentioning
confidence: 99%
“…PGM catalyze the interconvertion of glucose-1-phosphate (Glc-1-P) and Glc-6-P. The normal way to detect the activity of PGM was using Glc-1-P as substrates, glucose-6-phosphate dehydrogenase (G6PDH) as coupled enzyme, by detect the increasing absorbance values of NADH at 340 nm ( Nishinari et al, 2012 ; Wang & Zhang, 2010 ). This method was convenience and simple because G6PDH was commercially available and cost-effective.…”
Section: Introductionmentioning
confidence: 99%